O Dito e o interdito : o homoerotismo em "Uma leve simetria", de Rafael Bán Jacobsen - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Considering the literary work a reference for a time which presents subjects historically situated and ideologically modulated, this study aims to reflect on the formative sense linked to literary discourse and its possibilitiessince here we analyze in the novel Uma leve simetria, by Rafael Bán Jacobsen (2009), discursive elements that dictate and/or interdictthe homosexual relationship experienced by the characters Daniel Lipman and PedroGleick, a story set in a Jewish community in which these characters are followers. The research adopts a qualitative approach and its main objective is to analyze how the literary writing supported by social representations can be used as tools for social changes, leading the reader to oppose and critically evaluate prejudiced discourses related to homosexual individuals in condition of homosexuality which circulate in society.Therefore, we developed this study with the perspective of doing a work of symbolic representations of analysis in a socio-cultural view. This study aims also to examine the possibilities of Literature to act as a support tool of reflection on the constitution of sexual identity of those readers living in homosexuality condition. In this sense, this study deals with social representations and discourses conveyed in the work of Jacobsen on the homoerotism. The analysis of the work supports theories that suggest that the reader, being homoaffective or not, will be able to reflect on his/her own sexual identity. In this perspective, when dealing with events concerning both the subject and the society, itexpresses the representation of everyday life of today's society, once it retrieves common experiences of our daily lives. Finally, we seek to point out some possibilities for the applicability of the educational and social meaning of the literary work relating it to cultural aspects.
Keywords: Literatura brasileira; Romance contemporâneo; Homoerotismo; Literatura - Simetria; Brazilian literature; Contemporary romance; homoerotism; Literature - symmetry; LETRAS::LITERATURA BRASILEIRA; LETRAS::TEORIA LITERARIA